Transaksi Bisnis dalam Electronic Commerce (E-Commerce): Studi tentang Permasalahan Hukum dan Solusinya - M. Arsyad Sanusi (Jurnal Hukum IUS QUIA IUSTUM, 2001)
The progress of modem technology recently makes the transformation of Information and mode of communication among human beings become easy and direct, especially in the world of trade. In deed, the business facilities which can be obtained easily through e- commerce gives some advantages, but, at the same time, it also gives birth a number of crucial legal problems. First, the substantive problem swhich include problems of data massage authenticity, electronic signature, validity, privacy or confidentiality, security, and availability. Second,the procedural problems which are related to jurisdiction or forum. To solve such problems, weneed to prepare certain instruments which support the establish ment ofsafe, effective and beneficial e-commerce transaction for all parties involved. In addition, we have toper form reformation and uniformity of law by referring to UNCITRAL Model Law as a fundamental guidance.